Rigid Rod-like Viscoelastic Behaviors of Methyl Cellulose Samples with a Wide Range of Molar Masses Dissolved in Aqueous Solutions - Daiki Nakagawa; Erika Saiki; Yoshiki Horikawa; Toshiyuki Shikata (Molecules, 2024)
The viscoelastic behaviors of aqueous solutions of commercially available methyl cellulose (MC) samples with a degree of substitution of 1.8 and a wide range of weight average molar masses (Mw) were investigated over a wide concentration (c) range at some temperatures from −10 to 25 °C. The viscoelastic parameters useful to discuss the structure and dynamics of MC-forming particles in aqueous solutions were precisely determined, such as the zero-shear viscosity (η0), the steady-state compliance (Je), the average relaxation time (τw), and the activation energy (E*) of τw. Because previously obtained scattering and intrinsic viscosity ([η]) data revealed that the MC samples possess a rigid rod-like structure in dilute aqueous solutions over the entire Mw range examined, the viscoelastic data obtained in this study were discussed in detail based on the concept of rigid rod particle suspension rheology. The obtained Je−1 was proportional to the number density of sample molecules (ν = cNAMw−1, where NA means the Avogadro’s constant) over the ν range examined irrespective of Mw. The reduced relaxation time (4NAτw(3νJe [η]ηmMw)−1), where ηm means the medium viscosity, was proportional to (νL3)2, L; the average particle length depending on Mw for each sample was determined in a previous study; and the reduced specific viscosity (ηspNAL3(Mw [η])−1), where ηsp means the specific viscosity, was proportional to (νL3)3 in a range of νL3 < 3 × 102. These findings were typical characteristics of the rigid rod suspension rheology. Therefore, the MC samples behave as entangling rigid rod particles in the νL3 range from rheological points of view. A stepwise increase in E* was clearly observed in a c range higher than the [η]−1 value irrespective of Mw. This observation proposes that contact or entanglement formation between particles formed by MC molecules results in an increase in E*.